PENGGUNAAN E-MONEY DALAM E-COMMERCE SEBAGAI PENDUKUNG LESS CASH SOCIETY - Laksmi P., Kadek Wulandari; Permana, Gusti Putu Lestara (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2018)
The development of information technology causes changes in all fields. One of them is the development in the payment system, where the payment system which initially still in cash has been turned into non-cash. The use of non-cash money or electronic money (e-money) has been widely used by people in transactions, especially in transactions that are online or better known as electronic commerce (e-commerce). E-commerce itself is also one of the impact of the development of information technology. E-commerce itself allows people to buy goods, because they do not need to come to the store to transact simply with internet access is able to buy the desired goods, while for payment already can use e-money as a means of payment. With the use of e-money in e-commerce transactions can certainly support the government's program in reducing the use of cash in transactions known as Less Cash Society (LCS). The purpose of this research is to know the influence of e-money usage level in e-commerce transactions to LCS level. The benefits of this research are: 1) The community is expected to be more familiar with e-money and more often use it in transactions, 2) in e-commerce can support government programs namely Less Cash Society (LCS). The data source used is primary data and data type used is quantitative data collected by questionnaire. The data analysis technique used is Statistical Package For Social Sciences (SPSS). Results of data processing using SPSS obtained the result that the use of e-money in e-commerce has a very significant effect on LCS of 0.503.